Natural radionuclides in rocks of King George Island (West Antarctica) as tracers of chemical processes - Solecki, Andrzej; Tatur, Andrzej (Polish Polar Research, 2025)
During the austral summer of 2002/03, 253 gamma radiation spectrometric measurements of uranium, thorium, and potassium (further as U, Th, and K, respectively) content on outcrops of magmatic-sedimentary succession of the Admiralty Bay (King George Island) were performed. Low content and stable U/Th/K ratios were found in most cases in unaltered igneous rocks. Three examples of anomalous Th/K and U/K ratios were found in the Ezcurra Fault Zone, a quartz-pyrite lode of the Keller Peninsula, and a Paleogene paleosol at Cytadela Hill. In the first case, an enrichment in K was found to occur due to hydrothermal alterations in the fault zone. The high Th content in the quartz lode is evidence of volcanogenic leaching of K and, to some extent, U from the granodioritic rock. A significant mass loss during the leaching resulted in the enrichment of the inert Th content in the residuum. Modification of Th/K ratios due to chemical weathering was found in the Paleogene paleosol, where K leaching occurred. The K/Th ratio is a valuable tool for mapping hydrothermal alteration phenomena and locating Paleogene chemical weathering zones.